Propuesta de implementación de buenas prácticas de manufactura, en la microempresa productos lácteos santa ivonne, de la provincia de Cotopaxi del cantón Latacunga durante el periodo 2012 - Viracucha Pila, Ricardo Fernando (2013)
The Good Manufacturing Practices are principles that apply to all food handling processes processed and they are an essential tool to develop healthy and safe food for the consumer. In all type of establishment that elaborates food, either company or micro-company is increasingly necessary to adopt systems that allow ensure the sanitary quality of the finished product. This work was carried out on microenterprise Products Diary "SANTA IVONNE", dedicated to the production and marketing of fresh cheese which evaluated the current situation in which the micro company is using a checklist based on the requirements of Regulation of Good Manufacturing Practices for processed foods No. 3253 issued by the Constitutional Court in 2002 during the administration of Dr. Gustavo Noboa Bejarano, through the Official Gazette No. 696....